Thermal studies of solid 4-chlorobenzylidenepyruvates of heavy lanthanides(III) and yttrium(III) - Fernandes, N. S.; Carvalho, MAS; Melios, C. B.; Ionashiro, Massao [UNESP] (Kluwer Academic Publ, 2003)
Solid-state compounds of general formula LnL(3).2H(2)O, where Ln is heavier trivalent lanthanides and yttrium, L is 4-chlorobenzylidenepyruvate have been synthetised.On heating these compounds decompose in steps. They lose the hydration water in the first step and the thermal decomposition of the anhydrous compounds occurs with the formation of oxochloride (Eu, Gd); mixture of oxide and oxochloride that decrease with increasing of atomic number of metal (Tb-Tm); or oxide (Yb, Lu, Y) as final residue, up to 900degreesC. The dehydration enthalpies found for terbium, holmium, ytterbium and yttrium compounds were: 34.93, 42.40, 57.39 and 62.24 kJ mol(-1), respectively.
Keywords: 4-chlorobenzylidenepyruvate; heavier lanthanide; thermal decomposition